Factors Affecting the Settlement of BPJS Against the Approval Verifiers BPJS at Citama Hospital - Ikhlaq Muluk; M Natsir Nugroho; Wahyuni Dian Purwati (Syntax Corporation Indonesia, 2023)
The hospital claim process starts with completing the document file as a condition for submitting a claim by the hospital coding officer. A verifier verifies the claim file at the BPJS Center. Verification is researching and checking the claim's Completeness, validity, and feasibility. After verification, the claim file is sent to the Branch Office / District / City Operational Office of BPJS Kesehatan. The Completeness of the document file is an important part of the claim process. If the Hospital can meet the Completeness of the documents, it is likely that the faster the process of reimbursement of the cost of health services that have been provided. The method used in this study is the mixed method. The mixed method is a research method that combines quantitative methods with qualitative methods to be used together in a research activity so that more comprehensive, valid, reliable, and objective data are obtained. Hypothesis Results from First Hypothesis 1) Hypothesis Zero (Ho) There is no relationship between the Completeness of the inpatient medical records of the surgical care unit with the approval of the BPJS claim at Citama Hospital 2) Alternative Hypothesis (Ha) There is a relationship between the Completeness of the inpatient medical records of the inpatient care unit with the approval of the BPJS claim at Citama Hospital Based on the results of the Simple Regression in the previous section, it can be concluded that Ho was rejected, Ha received. The Completeness of the inpatient medical records of the inpatient care unit significantly affects the approval of BPJS claims at Citama Hospital.